Battery-Supercapacitor Current Control Using Fuzzy Supervisory with PI Controller for Electric Vehicle Application - Adnan Rafi Al Tahtawi; Muhammad Reihan Iskandar; Sofian Yahya; Toto Tohir; Dedi Aming (Jurnal Internasional Penelitian Teknologi Terapan, 2022)
The configuration of the battery-supercapacitor as a hybrid power source (HPS) is one solution to overcome the limitations of battery life, such as in an electric vehicle. To achieve battery energy savings when a supercapacitor is added, a control scheme is needed. This paper proposes a battery-supercapacitor current sharing control scheme using Fuzzy Supervisory Control (FSC). The FSC is designed to determine how much current of the battery and supercapacitor need to discharge based on the current requirement of the load. The output of the FSC will produce a reference current which is then controlled in the main closed-loop control using a Proportional-Integral (PI) controller. The control signal in the form of a duty cycle is then used to regulate the battery-supercapacitor current through a DC/DC converter. This control scheme is tested using a resistive load change scenario both simulation and experimental. The results show that the battery-supercapacitor current can be controlled according to the loading conditions.